Emerging History and trends of Medical Tourism in India (International Journal of Food and Nutritional Sciences, 2017)
Tourism is travel for predominantly recreational or leisure purposes or for the provision of services to support this leisure travel. Tourism has emerged during second world war. After second war, non-employment crisis has emerged. Tourism used as a tool to improve poverty and non-employment crisis.Hunziker and Krapf in 1941 defined tourism as ‘the sum of phenomena and relationships arising from travel and stay of non-residents in; so far as they do not lead to permanent residence and are not connected with any earning activity.’ But later this phase of tourism has undergone several changes. In today’s era we have know people to back up their lives and just travel across borders for years together. People travel across countries to attend just singular events, some to taste delicate red ant chutney from a corner of the Meghalaya forests, some travel across countries just for ayurvedic massages (Kerala) or travel across the world for thermal baths (Budapest). Well of course this is coupled with interesting conversations, learning about the other regions’ culture, lifestyle and food amongst several other things